Pengutan Moderasi Beragama Berbasis Konten pada Organisasi IPNU-IPPNU - Siti Asiyah (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2025)
Religious moderation is an important principle in maintaining social harmony that emphasizes balance, tolerance, and respect for differences amid religious and cultural diversity in Indonesia. The challenge of spreading extreme religious beliefs, especially among the younger generation, demands the strengthening of the values of religious moderation through an approach that is relevant to the times. Service activities for Strengthening Content-Based Religious Moderation at the IPNU-IPPNU Organization in Tunahan Keling Village, Jepara. Through the Asset Based Community Development ABCD method, the implementation of activities includes socialization of religious moderation, training in creating educational content with nuances of religious moderation, assistance in managing the organization's social media, and evaluating participants' understanding. The results of the activity impact increase in the understanding of IPNU-IPPNU members on the concept of religious moderation and their ability to produce and disseminate positive content that prioritizes the values of tolerance, nationality, and inclusive religious attitudes. This program contributes to forming a young generation that is digitally capable while being committed to maintaining the unity and harmony of religious people in the community of Tunahan Village.